Perceptions of caring behaviors by elderly residents in extended care facilities - Llasus, Ludy Sta Maria (ProQuest Information and Learning Company, 2002)
The purpose of this descriptive study was to describe elderly residents' perceptions of which caring behaviors they want exhibited by the nursing staff in extended care facilities. Consequently, this study was able to identify which caring behaviors are important and least important to this population. Using Jean Watson's Theory of Transpersonal Caring as the framework, this study utilized Wolf's Caring Behaviors Inventory instrument to answer the study's research questions. Forty-eight participants wanted nursing staff to demonstrate behaviors under the professional knowledge and skill dimension of the CBI. The sample also identified five most important and least important nurse caring behaviors. No significant difference was found between age, educational level and length of stay in the facility and perceptions of caring behaviors. This study's findings suggest gender difference in perceptions of caring behaviors.